Explication of screen culture - Dmitry Belyaev; Ksenia Aksenova (Arte y Sociedad)
The screen is rapidly becoming the dominant mode of modern culture, acting as a technological tool, a medium and a special, in its own way unique environment for the multidimensional human existence. This actualizes the study of the genesis of screen culture, the content and evolution of the formats of its representation both in the structure of human everyday life and in the historical continuum of culture.